Cost-effectiveness analysis of a proposed public health legislative/educational strategy to reduce tap water scald injuries in children. Issue 4 (8th August 2007) - Han, Ra K; Ungar, Wendy J; Macarthur, Colin
Abstract : Objective: To determine the cost effectiveness of a public health legislative/educational strategy to reduce tap water scalds in children less than 10 years of age. Design: Cost-effectiveness analysis conducted from the government perspective over a 10-year time horizon. Population: Children under 10 years of age in Ontario, Canada Interventions: Legislation to set thermostat settings on new domestic water heaters to lower temperatures (maximum 49°C) plus annual educational notices to utility customers versus status quo. Main outcome measures: The burden of tap water scalds, healthcare resource utilization, the cost and effectiveness of the proposed intervention, and the probabilities assigned to health outcomes were modeled in a decision analysis based on population-based data, patient charts, and the published medical literature. All costs and health outcomes beyond 1 year were discounted at 3%. Results: An estimated 182 children under 10 require medical care for tap water scald injuries annually in Ontario (13.98 per 100 000). Of these, 65 require emergency department (ED) care only (median cost C149 per injury), 103 require ED care with clinic follow-up (C577 per injury), 14 require hospital admission (C5203 per injury), and two require surgical skin grafting (C28 526 per injury). The estimated cost of the intervention was C51 000 annually, with a projected 56% reduction in tap water scald injuries. Over 10 years, the intervention group would show total costs of C1.17 million and 704 scalds, compared with C1.65 million and 1599 scalds in the status quo group. Therefore, the intervention would be cost saving, with an incremental ratio of C531 saved per scald averted. Sensitivity analyses showed that the intervention would remain cost saving through a wide range of variable estimates. Conclusions: Legislation to lower thermostat settings on domestic water heaters plus annual educational notices to utility customers would generate cost savings while reducing the morbidity from tap water scalds in children.